The Christmas thief [compact disc, unabridged] - Clark, Mary Higgins (Clark, Mary Higgins. Alvirah and Willy., 2004)
Alvirah Meehan and Reagan Reilly get in the middle of a case involving a beautiful eight-foot blue spruce that has been chosen to spend the holidays as Rockefeller Center's famous Christmas tree. The folks who picked the tree don't have a clue that attached to one of its branches is a flask chock-full of priceless diamonds that Packy Noonan, a scam artist just released from prison, had hidden there over twelve years ago.